Pengaruh Insentif, Kedisiplinan Kerja dan Pengembangan Karier Terhadap Semangat Kerja Karyawan pada PT. Mega Finance Makassar - Irianti Irianti; Syarifuddin Syarifuddin; Andi Haerani (Jurnal Manajemen Informatika & Teknologi, 2025)
This research discusses the influence of incentive giving, working discipline and career development of the employee spirit at PT. Mega Finance Makassar. The study aims to analyse the influence of incentive assistance, work discipline and career development on employee morale, analyse partially linked variables, analyse simultaneous associated variables As well as analyzing the related variables that most influence the work of employees at PT. Mega Finance Makassar. The population in this research is the company and its employees in PT. Mega Finance Makassar amounted to 40 people. Sampling is carried out using the total sampling technique. Techniques of collecting data with questionnaires, whereas data analysis techniques using multiple linear regression analyses, classical assumptions (test normality, multicholinerity test, heteroskedastisity Test), statistical tests (t- test, F-test and determination test). Based on the results of a double linear regression analysis of the T test acquired findings by partial incentives to the employee spirit of PT. Mega Finance Makassar, while work discipline and career development are not significant. From the simultaneous trial results of incentive, work discipline and career development have significant effect on the employee spirit of PT. Mega Finance Makassar where the value of F count > F table. Incentives have the most dominant influence on the employee spirit of PT. Mega Finance Makassar acquired R Square value of 0.255, which means the dependent variable can be requested by an independent variable of 25.5% while the remainder is 74.5% Requested by another variable outside the model.